Volumetric indices of the left ventricle in patients with ischemic heart disease - Sheĭretova, E; Garcheva, M; Khadzhikostova, Kh; Babeva, S (Khirurgiia, 1989)
In addition to the conventional indices of radionuclide angiography with ECG-gait in equilibrium, the authors determined the volume indices of the left ventricle at rest by the so-called nongeometric method in 30 patients with ischemic heart disease. Patients without myocardial infarct (13 subjects) had decreased total left-ventricular ejection fraction (EF), as a result of increase in the end systolic volume index (ESVI) in one of the tested patients. Changes in the regional fractions and in the wall kinetics were detected in 6, resp. in 8 patients. Patients with myocardial infarct--13 subjects--had decreased total left ventricular EF, as a result increased ESVI in 4 patients. Disturbances in the regional fraction and in the wall kinetics had 9 patients. Estimated for the whole group, the mean ESVI level was significantly higher than in the former group of patients. Patients with postinfarction aneurysm, in addition to the marked decrease of the total left ventricular EF, had increased and-systolic and diastolic volume index, which in some of the patients was associated with reduced stroke volume index. The minute flow levels were significantly lower than in the former two groups. Determination of the volume indices is an important supplement to the efforts to gain precise information on the functional state of the left ventricle and for evaluation of the hemodynamics and of the effect of complications which occur with the advancing of the ischemic heart disease.